The Link between Institutional Influences and Competitive Advantages Generated by Strategic CSR: The Case of Hyundai Motor Company in South Korea - Moon, Hyung-Ju (2013)
Corporate Social Responsibility is no longer a new concept for companies; many of them now employ CSR as a strategic tool to generate competitive advantages. Although carrying out CSR activities is generally based on discretion, it can be also formed by the institutional environment in which a firm belongs. Therefore, not only can the institutional condition influence a company’s strategic approach to CSR, but also the competitive advantages generated by the company’s strategic CSR can be maintained or weakened by the institutional context. This dissertation has a purpose to understand and examine the dynamics between a certain institutional environment and competitive advantages generated by a company’s strategic CSR with an interpretivism stance. In order to achieve the aim, this paper explores ‘Hyundai Motor Company (HMC)’ and South Korea as a case study for the selected period. Although the direction of HMC’s CSR strategies seems to be on the right track towards achieving competitive advantages, the institutional environment around HMC does not properly support HMC, especially the eco-friendly technology development and labour issues. Moreover, the lack of consumer rights protections also leads HMC to lose its intangible resources – reputation and image.